2019
DOI: 10.1080/14616688.2019.1600007
|View full text |Cite
|
Sign up to set email alerts
|

Internet representations of voluntourism fail to effectively integrate tourism and volunteering

Abstract: Voluntourism as a form of philanthropic tourism has become an increasingly popular research topic but there is a paucity of literature on the complex interplay between voluntourism and the internet. Specifically, there is sparse evidence on how the internet mediates ideas and representations of voluntourism. Building on prior research in the information search field, we examine the online representation of voluntourism in South Africaa popular destination for voluntourists. Querying a popular search engine usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 64 publications
0
3
0
1
Order By: Relevance
“…The online imaginaries of volunteer tourism created by organisations are crucial for the influence they wield. Inversini et al (2019) applied the social representation theory to analyse the content of websites managed by volunteer tourism organisations in South Africa. The study revealed that tourism and volunteering are cast as key elements of what is broadcasted as a cultural experience.…”
Section: Organisations: Mediating the Relationsmentioning
confidence: 99%
“…The online imaginaries of volunteer tourism created by organisations are crucial for the influence they wield. Inversini et al (2019) applied the social representation theory to analyse the content of websites managed by volunteer tourism organisations in South Africa. The study revealed that tourism and volunteering are cast as key elements of what is broadcasted as a cultural experience.…”
Section: Organisations: Mediating the Relationsmentioning
confidence: 99%
“…Defines social representation as an approach that describes how a concept or idea is understood, believed, and implemented by a social group [24] [25]. In simple terms, social representation is how a concept is understood, believed, and carried out by a group of people [26]. Social representation theory believes that individuals and society influence and interact with each other in constructing meaning and reality in society.…”
Section: B Social Representation Theorymentioning
confidence: 99%
“…Social representation is a collective phenomenon related to the community coordinated by individuals in their daily speech and actions. Social representation is the unity of thoughts and feelings expressed in actors' verbal and open behavior objects for social groups [26]. Social representation theory is a valuable tool in community-based health research [27].…”
Section: B Social Representation Theorymentioning
confidence: 99%
“…O número de pessoas com acesso à internet no mundo corresponde a aproximadamente 4 bilhões de pessoas, ou seja, mais da metade da população mundial (Kemp, 2018), sendo o uso desta na busca de informações para a escolha do destino turístico cada vez mais frequente a fim de obter informações corretas e relevantes sobre a viagem (Inversini, Rega, & Zyl, 2019), melhorando a experiência turística (Adeola & Evans, 2019).…”
Section: Introductionunclassified